Implicitly strengthened task‐irrelevant stimulus‐response associations modulate cognitive control: Evidence from an fMRI study. Issue 2 (23rd November 2015) - Xia, Tiansheng; Li, Hui; Wang, Ling
Abstract: The dynamics of cognitive control have been investigated by the proportion congruency effect. However, the theory that this effect is due to attentional modulation has been challenged by contingency learning accounts. This raises the question of how the cognitive control system operates during and after increasing the strength of task‐irrelevant stimulus‐response (S‐R) associations. We employed a novel paradigm that elicits positive and reversed Simon effects via task rule manipulations, and combined it with a between subjects proportion congruency manipulation. The pattern of enhancement and reversal of the positive and reversed Simon effects across conditions suggested that participants used strengthened task‐irrelevant S‐R associations to predict responses. Functional neuroimaging identified proportion congruency effects that interacted with task S‐R associations, showing greater activity when strengthened task‐irrelevant S‐R associations conflicted with task‐defined S‐R associations in frontoparietal regions, including bilateral superior parietal lobule (SPL) and dorsal premotor cortex (dPMC), presupplementary motor area/anterior midcingulate cortex (Pre‐SMA/aMCC), and left dorsolateral prefrontal cortex (DLPFC). These results suggest that the aMCC and DLPFC shifted to responding mainly to the conflict induced by the strengthened irrelevant S‐R associations. The SPL and dPMC might represent the strengthened irrelevant S‐R associations. Hum Brain Mapp 37:756–772, 2016 . ©2015 Wiley Periodicals, Inc.